LEARNING ENGLISH FOR INDONESIAN ADULT LEARNERS: WHAT THEY THINK AND WHAT THEY EXPERIENCE - Agustina, Sheila; Fediyanto, Niko (J-ELLiT (Journal of English Language, Literature, and Teaching), 2021)
Learning English as a foreign language has always been a challenge for many learners in Indonesia. In the past, learning English in classrooms might not be as interesting and varied as it is now. Thus, this research aimed at describing adult learners’ perception on learning English and their experience when learning it during school. The participants of this research were 15 school staff, aged 20 to 50 years old, who were taking English course for employees at the time. Under qualitative research, the researcher used close-ended questionnaire, field-note, and documentation as the research instruments to collect the data from the participants. Some simple statistics was used only to find out the salient patterns from the data which would later be explained descriptively. The findings indicated that despite the participants being interested in learning English, they really had a hard time learning it and went through such monotonous English teaching and learning in the past. This research also managed to expose the participants’ difficulties in composing simple sentences orally and in writing. Although the generalization could not be simply made from this research, the result of the research demonstrated some problems in English language learning at school which made learners could not perform the language on an ongoing basis.